Task-Specific Recognition Signals Are Located on the Legs in a Social Insect - Wang, Qike; Goodger, Jason Q. D.; Woodrow, Ian E.; Chang, Le; Elgar, Mark A. (Frontiers in Ecology and Evolution, 2019)
Task allocation ensures a high level of organization within social insect colonies. Workers reveal their task assignment through cuticular hydrocarbon (CHC) signals. The source and chemical composition of these signals are largely unknown. We ask whether task recognition signals are located on particular body parts of workers of Australian meat ants (Iridomyrmex purpureus). We analysed the CHC profile on the antennae, legs and abdomens of workers engaged in different tasks. Discriminant analysis showed that the leg profile is the best indicator of task identification. Behavioural assays confirmed this finding: workers typically reacted differently to non-nestmates engaged in different tasks, but not if the CHCs on the legs of their opponents were removed by a solvent. Lasso and Elastic-Net Regularized Generalized Linear Model (GLMNET) revealed which CHC components show the highest correlation in task and nestmate recognition, suggesting that social insects can simultaneously convey different CHC signals on different body parts, thereby allowing efficient signaling and signal perception.